Effects of a kinesiotherapy intervention protocol with exergame on improving muscle strength, balance and respiratory muscle strength in patients with stroke (Research, Society and Development, 2024)
Objective: to evaluate the effects of a kinesiotherapy intervention protocol with exergame in patients with stroke. Materials and Methods: This study is characterized by being applied, experimental, longitudinal, with exploratory and descriptive objectives and sought to investigate the effects of exergames in patients with Stroke (CVA). The sample consisted of five participants (two men and three women) aged between 38 and 77 years, living in Erechim/RS. The participants underwent a kinesiotherapy intervention protocol with exergame during 10 sessions, held twice a week, for 60 minutes each session over five weeks. The evaluations performed were through the Time Up and Go (TUG) test to assess dynamic balance, analog dynamometry for muscle strength of upper and lower limbs, and manovacuometry to assess respiratory muscle strength. Results: Gain in muscle strength and improvement in respiratory muscle strength were observed in comparison with pre- and post-application of physiotherapy treatment. Conclusion: The findings of this study show that the kinesiotherapy protocol with exergames showed evidence of improvement in muscle strength and respiratory muscle strength.